1995
DOI: 10.1038/bjc.1995.166
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tumour-suppressor gene Rb, apoptosis-suppressing protein Bcl-2 and c-Myc have no independent prognostic value in renal adenocarcinoma

Abstract: Summary The expression of retinoblastoma (Rb), c-Myc and Bcl-2 proteins was studied by immunohistochemical methods in 104 cases of renal adenocarcinoma. One tumour was completely negative for Rb protein and altered expression pattern was detected in 36% of cases. A low fraction of Rb-positive nuclei was related to high grade (P = 0.016) and high mitotic index (P = 0.012). Twenty-eight per cent of the tumours expressed c-Myc in cancer cell nuclei and 87% showed cytoplasmic positivity. Cytoplasmic expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 20 publications
6
29
2
Order By: Relevance
“…Previous studies in RCC have not included DJ-1 analysis for comparison and few observations have been presented for cMyc, except that immunohistochemical detection of cMyc had no independent prognostic value 48 Regarding hTERT one study found no correlation between hTERT RNA expression and stage or presence of metastasis 23 and in another study telomerase activity was unrelated to stage or grade 49 supporting the data we present here.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies in RCC have not included DJ-1 analysis for comparison and few observations have been presented for cMyc, except that immunohistochemical detection of cMyc had no independent prognostic value 48 Regarding hTERT one study found no correlation between hTERT RNA expression and stage or presence of metastasis 23 and in another study telomerase activity was unrelated to stage or grade 49 supporting the data we present here.…”
Section: Discussionsupporting
confidence: 79%
“…In fact, recent studies reported that apoptosis-related molecules, such as p53, Bcl-2, Bax and c-Myc, play no functional role in the progression of RCC. [2][3][4][5] These findings suggest that RCC may acquire antiapoptotic activity against several therapies through a unique mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…1) Moreover, different from other malignant tumors, there was no significant association between the prognosis of patients with RCC and the expression of apoptosis-related molecules, such as p53, Bcl-2, Bax and c-Myc. [2][3][4][5] Accordingly, the mechanism of resistance to therapy-induced apoptosis in RCC remains largely unknown.…”
Section: Introduction Of Clusterin Gene Into Human Renal Cell Carcinomentioning
confidence: 99%
“…142,143 A similar low frequency of bcl-2 expression is also found in transitional cell carcinomas of the renal pelvis and in renal cell adenocarcinoma. 144,145 Other Tumors…”
Section: Urogenital Carcinomasmentioning
confidence: 99%